THE EFFECT OF COURSE REVIEW HORAY COOPERATIVE LEARNING MODEL WITH WORD CARD MEDIA ON DESCRIPTIVE TEXT WRITING SKILLS - putri, sherly dinanda; Retnosari, Ira Eko (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2025)
A teacher plays an important role in improving students’ knowledge and skills. Knowledge is a collection of information, facts, and understanding from experience, education, or research. Knowledge can be theoretical or practical and covers various fields, such as natural sciences, social sciences, humanities, and technology. An indicator of success in teaching is the effectiveness of learning, including in Indonesian subjects. Indonesian subject learning increases students’ interest in writing. The Course Review Horay (CRH) model effectively increases student motivation and learning outcomes. This research analyzes the influence of CRH with word card media on the descriptive text writing skills of 2nd-grade elementary school students. The method used was quantitative, with a quasi-experimental design (Quasi-Experimental Research) using a post-test-only control design, involving 54 students in 2nd grade of classes A and C. Maximum control class 71, minimum 25; experiment maximum 83, minimum 25. Analysis shows that the average descriptive text writing skill of CRH students without word cards is 45.63, showing the impact of the CRH model with word cards in the SDN Margorejo 1/403 Surabaya class